Subpopulation Triage: How to Allocate Conservation Effort among Populations - McDONALD-MADDEN, EVE; BAXTER, PETER W.J.; POSSINGHAM, HUGH P. (Conservation biology, 2008)
Threatened species often exist in a small number of isolated subpopulations. Given limitations on conservation spending, managers must choose from strategies that range from managing just one subpopulation and risking all other subpopulations to managing all subpopulations equally and poorly, thereby risking the loss of all subpopulations. We took an economic approach to this problem in an effort to discover a simple rule of thumb for optimally allocating conservation effort among subpopulations. This rule was derived by maximizing the expected number of extant subpopulations remaining given n subpopulations are actually managed. We also derived a spatiotemporally optimized strategy through stochastic dynamic programming. The rule of thumb suggested that more subpopulations should be managed if the budget increases or if the cost of reducing local extinction probabilities decreases. The rule performed well against the exact optimal strategy that was the result of the stochastic dynamic program and much better than other simple strategies (e.g., always manage one extant subpopulation or half of the remaining subpopulation). We applied our approach to the allocation of funds in 2 contrasting case studies: reduction of poaching of Sumatran tigers (Panthera tigris sumatrae) and habitat acquisition for San Joaquin kit foxes (Vulpes macrotis mutica). For our estimated annual budget for Sumatran tiger management, the mean time to extinction was about 32 years. For our estimated annual management budget for kit foxes in the San Joaquin Valley, the mean time to extinction was approximately 24 years. Our framework allows managers to deal with the important question of how to allocate scarce conservation resources among subpopulations of any threatened species. /// Las especies amenazadas a menudo existen en número reducido de subpoblaciones aisladas. Dadas las limitaciones en el gasto para conservación, los manejadores deben seleccionar estrategias que van desde el manejo de solo una subpoblación, dejando a las demás en riesgo, hasta el manejo de todas las subpoblaciones por igual y deficientemente, con el consiguiente riesgo de que se pierdan todas las subpoblaciones. Utilizamos un enfoque económico para este problema en un esfuerzo por descubrir un principio general simple para la asignación óptima de esfuerzos de conservación entre subpoblaciones. Esta regla se derivó de la maximización del número esperado de subpoblaciones sobrevivientes de n subpoblaciones manejadas. También derivamos una estrategia optimizada espaciotemporalmente mediante programación estocástica. El principio general sugirió que se debe manejar un mayor número de subpoblaciones si el presupuesto aumenta o si disminuye el costo de reducción de las probabilidades de extinción local. El principio funcionó bien contra la estrategia exacta óptima que fue el resultado del programa estocástico dinámico y funcionó mucho mejor que las otras estrategias simples (e.g., manejar siempre una subpoblación existente o la mitad de la subpoblación remanente). Aplicamos nuestro método a la asignación de recursos en 2 estudios de caso contrastantes: reducción de la cacería furtiva de tigres de Sumatra (Panthera tigris sumatrae) y la adquisición de hábitat para zorros (Vulpes macrotis mutica). Con nuestro presupuesto anual estimado para el manejo del tigre de Sumatra, el tiempo medio hasta la extinción fue de 32 años aproximadamente. Con nuestro presupuesto anual estimado para el manejo de V. m. mutica, el tiempo medio hasta la extinción fue de 24 años aproximadamente. Nuestro marco de referencia permite que los manejadores aborden la pregunta de cómo asignar recursos escasos para la conservación entre subpoblaciones de cualquier especie amenazada.